2011
DOI: 10.1111/j.1600-0714.2011.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of canonical and non‐canonical Wnt ligands in ameloblastoma

Abstract: Differential expression of Wnt ligands in different ameloblastoma subtypes suggests that the canonical and non-canonical Wnt pathways are selectively activated or repressed depending on the tumor cell differentiation status. Canonical Wnt pathway is most likely the main transduction pathway while Wnt-1 might be the key signaling molecule involved in ameloblastoma tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 43 publications
(93 reference statements)
1
40
0
Order By: Relevance
“…Additionally, it has been reported that WNT7A expression is frequently reduced or absent in lung cancers when compared with normal lung and mortal, short-term bronchial epithelial cultures [32]. By Immunohistochemical examination in 72 cases of ameloblastoma, an odontogenic epithelial neoplasm, WNT7A was also found absent [33]. On taking advantage of the free database containing in the cBioPortal for Cancer Genomics, WNT7A mRNA expression (z-score) was also analyzed in the provisional TCAG database from 190 patients with Cervical squamous cell carcinoma (CSCC).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, it has been reported that WNT7A expression is frequently reduced or absent in lung cancers when compared with normal lung and mortal, short-term bronchial epithelial cultures [32]. By Immunohistochemical examination in 72 cases of ameloblastoma, an odontogenic epithelial neoplasm, WNT7A was also found absent [33]. On taking advantage of the free database containing in the cBioPortal for Cancer Genomics, WNT7A mRNA expression (z-score) was also analyzed in the provisional TCAG database from 190 patients with Cervical squamous cell carcinoma (CSCC).…”
Section: Discussionmentioning
confidence: 93%
“…Wnt/β‐catenin signalling is involved in ameloblastoma tumorigenesis and progression . Furthermore, it is widely accepted that Wnt/β‐catenin signalling can mediate mechanotransduction in cells .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signalling is involved in ameloblastoma tumorigenesis and progression. 6 Furthermore, it is widely accepted that Wnt/βcatenin signalling can mediate mechanotransduction in cells. 9 An immunofluorescence assay showed MMP-2, MMP-9 and RANKL were expressed in hTERT + -AM cells, which presented punctate cytoplasmic staining.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the ghost cells showed strong positive reaction to antibodies against hair proteins. Moreover, Wnt signaling is believed to be responsible for the increase β-catenin expression in the cytoplasm and nucleus of epithelial cells in close proximity as well as the nuclear localization of Lef-1 13.…”
Section: Discussionmentioning
confidence: 99%